أثر الكوارث الطبيعية على الوضع الصحي للعامة في الدولة العباسية - شوانة, خولة; خالدي, مسعود (جامعة الوادي - University of Eloued, 2022)
تعرضت الدولة العباسية خلال الفترة الوسيطة لموجات من الكوارث الطبيعية كالفيضانات والسيول والزلازل وغيرها من الكوارث شأنها شأن بقيت دول العالم الإسلامي أنذاك، بغض النظر عن نوعها أو حدود انتشارها فقد راح ضحيتها الكثير من الأهالي وذلك لحدوثها المفاجئ وتأثيرها السلبي على المجتمع البشري وحالته الصحية، حيث أنها غالبا ما فاقت قدراته واستطاعته فتأثرت بذلك أنشطته الاقتصادية. في أغلب الأحيان عمت تلك الكوارث عددا من المدن والقرى في آن واحد ما يجعل الأمر أكثر سوءا. من منطلق أن الأزمات الصحية لا تحدث بطريقة تلقائية وانما هي نتيجة لعوامل طبيعية وبشرية تزامنت وتفاعلت مع غياب الإجراءات الوقائية والاحترازية. كان لتكرار حدوث الكوارث الطبيعية في الدولة العباسية خلال القران الرابع هجري أثر كبير على المعالم الصحية ومن ثم الديموغرافية للعامة، ما خلف آثارا على الجانب الاقتصادي بصفة خاصة باعتبار ان الانسان هو المنتج والمستهلك. جاءت هذه الدراسة لبيان المضاعفات المرضية الناتجة عن حدوث مختلف الكوارث الطبيعية ومن ثم مدى تأثر الجانب الاقتصادي بالحالة الصحية للعامة باعتبارهم الحلقة الأضعف في التركيبة السكانية. During the intermediate period, the Abbasid state was subjected to waves of natural disasters such as torrential rains, torrential rains, earthquakes and other disasters, similar to the rest of the Islamic world, regardless of its type or the extent of its spread, many people have been killed due to its sudden occurrence and its negative impact on human society and its health condition, as it usually exceeded its capabilities and ability, thus affecting its economic activities. In most cases, these disasters affected a number of cities and villages at the same time, which would have made the matter worse. On the grounds that health crises are not automatic, but are the result of natural and human factors that coincided and interacted with the absence of preventive and precautionary measures. The recurrence of natural disasters in the Abbasid state during the fourth century AH had a significant impact on the health and demographic parameters of the public, which left effects on the economic aspect in particular, given that man is the producer and the consumer. This study came to show the pathological complications resulting from the occurrence of various natural disasters, and then the extent to which the economic aspect is affected by the health status of the public.
مقال
Keywords: الكوارث الطبيعية، الأزمات الصحية، الأوبئة، العامة، الدولة العباسية; Natural disasters, health crises, epidemics, public , Abbasid state